2010
DOI: 10.1002/ccd.22698
|View full text |Cite
|
Sign up to set email alerts
|

Erroneous placement of central venous catheter in the subclavian artery: Retrieval and successful hemostasis with a femoral closure device

Abstract: Central venous catheter (CVC) placement, even if performed under duplex scan control, may be associated with incidental arterial injury leading to increased morbidity, mortality, and prolonged hospital stay. Erroneous CVC placement in the carotid or subclavian arteries has been usually treated surgically because those puncture sites may not be efficaciously compressed manually. However, surgery in this setting may be challenging because of difficulty of access for the catheters positioned in the subclavian art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…24 The most likely scenario in which this problem would arise is after catheterization of the subclavian or internal jugular vein in critically ill patients, procedures that are complicated by inadvertent adjacent arterial puncture in up to 8% of cases. 253 In addition to placement of central venous catheters for the resuscitation of critically ill patients, noncompressible veins may be accessed during medical care for placement of pacing or defibrillation leads, dialysis catheters, pulmonary artery catheters, or transcatheter heart valve placements. Notably, a patient undergoing one of these procedures may be less functional and more ill than the general population in which intravenous alteplase has been studied to date, and the ratio of risks to potential benefits in this subgroup may be substantially different.…”
Section: Arterial Puncture Of Noncompressible Vessels In the Precedinmentioning
confidence: 99%
See 1 more Smart Citation
“…24 The most likely scenario in which this problem would arise is after catheterization of the subclavian or internal jugular vein in critically ill patients, procedures that are complicated by inadvertent adjacent arterial puncture in up to 8% of cases. 253 In addition to placement of central venous catheters for the resuscitation of critically ill patients, noncompressible veins may be accessed during medical care for placement of pacing or defibrillation leads, dialysis catheters, pulmonary artery catheters, or transcatheter heart valve placements. Notably, a patient undergoing one of these procedures may be less functional and more ill than the general population in which intravenous alteplase has been studied to date, and the ratio of risks to potential benefits in this subgroup may be substantially different.…”
Section: Arterial Puncture Of Noncompressible Vessels In the Precedinmentioning
confidence: 99%
“…253 The common clinical observation of increased bleeding in anticoagulated patients who have central venous catheters placed and the potential consequence of uncontrollable and life-threatening hemorrhage from a noncompressible vessel likely justify this exclusion criterion, although there is no existing literature to support or oppose this recommendation. Although there are treatments available, that is, surgical procedures or endovascular intervention (eg, percutaneous arterial closure device placement, balloon tamponade, or use of covered stents), 254 they are not solutions to the problem because these procedures would confer significant bleeding risks to patients who receive thrombolytics.…”
Section: Arterial Puncture Of Noncompressible Vessels In the Precedinmentioning
confidence: 99%
“…Individuals may present with significant haematoma which would mandate a surgical evacuation, whilst other patients may be acutely unwell or will have other morbidities making the endovascular advantages of minimal invasiveness and avoidance of a general anaesthetic attractive. Endovascular management was only marginally less successful in this review and may also be more appropriate if the injury involves the medial subclavian artery as this may be difficult to access surgically (36). Diameter of the CVC device and the concurrent anticoagulation status of patients must also be considered when determining the most appropriate management option.…”
Section: Discussionmentioning
confidence: 94%
“…[ 27 30 ] The choice of one VCD instead of another must be individualized according to local factors (eg, vessel anatomy, tortuosity, presence of calcifications, plaques, and bifurcations) and most importantly according to the operator's knowledge of the device's characteristics. Schutz et al [ 31 ] described the case of a 79-year-old patient presenting with cardiogenic shock due to erroneously placed CVC in the right subclavian artery, in whom the hemostasis was obtained with the insertion of a 8 Fr Angioseal TM closure device. Alternative treatment for unintended puncture of small arteries such as internal mammary artery and inferior thyroid artery is its selective embolization [ 8 , 17 , 19 ] : Chemelli et al [ 6 ] reported 5 patients with internal mammary artery bleeding after subclavian vein puncture who were successfully treated through embolization with microcoils, with no procedure-related complications.…”
Section: Discussionmentioning
confidence: 99%